Swimming pools and similar environments - World Health Organization; World Health Organization (Guidelines for safe recreational water environments, 2006)
Volume 2 of the Guidelines explains requirements to promote safe use concepts and practices, including health-based targets and minimum procedures. It also covers a substantive revision of approaches to ensuring the microbial safety of wastewater used in agriculture. It introduces health impact assessment of new wastewater projects.
Keywords: Swimming pools : Standards; Water quality : Analysis; Environmental health